Engineering defect‐enabled 3D porous MoS2/C architectures for high performance lithium‐ion batteries. Issue 8 (7th March 2020) - Tao, Kai; Wang, Xiangfei; Xu, Yifeng; Liu, Jing; Song, Xuefeng; Fu, Chaopeng; Chen, Xiaoqi; Qu, Xingzhou; Zhao, Xiaofeng; Gao, Lian
Abstract: Designing defect‐rich MoS2 /C architectures with three‐dimensional (3D) porous frame effectively improve the electrochemical performance of lithium‐ion batteries (LIBs) owing to the improved conductivity and decreased diffusion distance of Li + ions for lithium storage. Herein, we report a reliable morphology engineering method combining with tunable defects to synthesize defect‐rich MoS2 nanosheets with a few layers entrapped carbon sheath, forming a 3D porous conductive network architecture. The defect‐rich MoS2  nanosheets with expanded interlayers can provide a shortened ion diffusion path, and realize the 3D Li +  diffusion with faster kinetics. A 3D conductive interconnected carbon network is able to improve interparticle conductivity, concurrently maintaining the structural integrity. Benefiting from these intriguing features, the as‐prepared MoS2 /C architectures exhibit excellent electrochemical performance: a high reversible capacity of 1163 mAh g −1  at a current density of 0.1 A g −1  after 100 cycles and a high rate capability of 800 mAh g −1  at 5 A g −1 . Defect content in MoS2 /C architectures can be obtained by changing H2  concentration. Compared with the counterparts with few defects, the defect‐rich MoS2 /C architectures show improved electrochemical stability with a superior cycle life, illustrating a highly reversible capacity of 751 mAh g −1 at 0.5 A g −1 after 500 cycles.